Kelembagaan Koperasi Syariah dalam Perspektif Sistem Ekonomi Islam Taqiyuddin an-Nabhani - Dadan Hamdani (LPPM Universitas Koperasi Indonesia, 2026)
This study aims to analyze the institutional framework of Islamic cooperatives from the perspective of the Islamic Economic System proposed by Taqiyuddin an-Nabhani. Islamic cooperatives, as community-based economic institutions, play a strategic role in promoting distributive justice and social welfare. However, in practice, many Islamic cooperatives still adopt capitalist economic principles, particularly in terms of ownership structure, management, and profit orientation. This research employs a qualitative method using a library research approach by examining the works of Taqiyuddin an-Nabhani as well as relevant literature on Islamic cooperatives and Islamic economics. The findings reveal that, according to an-Nabhani, the Islamic economic system emphasizes a clear distinction between individual ownership, public ownership, and state ownership. Within this framework, Islamic cooperatives are categorized as part of individual economic activities and must fully comply with Islamic legal principles in contractual arrangements, capital management, and profit distribution. The study concludes that strengthening the institutional foundation of Islamic cooperatives should be directed toward comprehensive adherence to the Islamic economic system rather than partial implementation of sharia principles. Therefore, Islamic cooperatives are expected to function not merely as profit-oriented entities but as institutions that embody Islamic values holistically.